It Takes a Group to Design but a Larger Community to Implement: Social Justice Language Education-Oriented Framework in Costa Rica - Rojas-Alfaro, Roberto; Ramirez-Casalvolone, Natalia (Pensamiento Actual, 2024)
While social justice education (SJE) is increasingly recognized as educationally essential for students’ academic and personal success, its full integration into K-12 education continues to face barriers, including resistance to discussing certain SJE topics. Using group interviews with five regional- and two national-level English-as-a-foreign-language (EFL) advisers tasked with leadership and curriculum advocacy in Costa Rica, this study explored their responses to proposed SJE-themed curriculum materials for online and offline education. Findings include concerns around the practical challenges of adding tasks to already-overburdened teachers’ workloads, aligning curricula with mandated educational benchmarks, and apprehension about introducing certain SJE topics, especially around sexuality and socioeconomic status. Recommendations include leadership support for focused SJE implementation and increased stakeholder input around developing and navigating real or anticipated SJE resistance in certain social sectors and refining proposed SJE materials to meet educational mandates without adding to teacher workloads.